Mitophagy and Oxidative Stress in Cancer and Aging: Focus on Sirtuins and Nanomaterials. (9th May 2019) - Vernucci, Enza; Tomino, Carlo; Molinari, Francesca; Limongi, Dolores; Aventaggiato, Michele; Sansone, Luigi; Tafani, Marco; Russo, Matteo A.
Abstract : Mitochondria are the cellular center of energy production and of several important metabolic processes. Mitochondrion health is maintained with a substantial intervention of mitophagy, a process of macroautophagy that degrades selectively dysfunctional and irreversibly damaged organelles. Because of its crucial duty, alteration in mitophagy can cause functional and structural adjustment in the mitochondria, changes in energy production, loss of cellular adaptation, and cell death. In this review, we discuss the dual role that mitophagy plays in cancer and age-related pathologies, as a consequence of oxidative stress, evidencing the triggering stimuli and mechanisms and suggesting the molecular targets for its therapeutic control. Finally, a section has been dedicated to the interplay between mitophagy and therapies using nanoparticles that are the new frontier for a direct and less invasive strategy.